Retracted: Financial Literacy, Ponzi and Pyramid Scheme in Indonesia - Hidajat, Taofik (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
The aim of this research is to examine empirically the influence of financial literacy on investment decisions through ponzi and pyramid schemes. Variables embedded were Social Economic Characteristics, Financial Literacy and Investments Decision. The population of this study were the people who invest their money through a Ponzi scheme and pyramid scheme. The sampling method applied was a snowball sampling of 43 respondents. Based from the research result, it was concluded that social economic characteristics, positively influences financial literacy. While, financial literacy influenced investment decision through ponzi and pyramid schemes. It is freaky because the people with good financial literacy (job occupation, education, gender and income) are still trapped under these junk investment trick modes. It was assumed that there were the other factors as the example, psychological factor like individual greed that influenced the financially literate people to invest through both junk investment schemes. It was also suggested a modification in financial literacy measuring because the existing financial literacy measuring tools had not been able to accommodate the understanding of ponzi and pyramid scheme investment.